The Role of the Gut Microbiome in Exercise-Induced Inflammation and Recovery: A Narrative Review - Dudek, Stanisław; Koziak, Weronika; Bętkowska, Aleksandra; Kornacka, Agata; Szostak, Kamila; Tomaka, Rafał; Makieła, Michalina; Dudek, Wojciech; Byra, Anna (Quality in Sport, 2025)
Background Exercise-induced inflammation is a complex physiological response influenced by both the intensity of physical activity and the gut microbiome. While moderate exercise enhances immune function and microbial diversity, excessive training can lead to gut dysbiosis, increased intestinal permeability, and chronic inflammation. Objective This review examines the interplay between the gut microbiome, exercise-induced inflammation, and recovery. It explores the mechanisms by which gut microbes influence immune regulation, metabolic adaptation, and muscle repair, while also identifying potential nutritional strategies to optimize gut health and enhance post-exercise recovery. Results Findings suggest that moderate exercise enhances microbial diversity and promotes an anti-inflammatory immune profile. Conversely, excessive training induces gut dysbiosis, increases intestinal permeability, and elevates inflammatory cytokines. Nutritional interventions, particularly probiotic and prebiotic supplementation, polyphenol-rich foods, dietary fiber, and omega-3 fatty acids, have been shown to mitigate gut permeability, enhance SCFA production, and accelerate immune recovery. Conclusion The gut microbiome plays a critical role in regulating exercise-induced inflammation and recovery, influencing immune responses, metabolic efficiency, and muscle repair. Integrating microbiome-targeted nutritional strategies may optimize gut health, enhance recovery, and improve overall athletic performance. Future research should explore personalized microbiome-based interventions, considering individual variability in microbiota composition, training load, and dietary habits.